Global economy: USA and China leading the way, Europe lagging behind - Claus Michelsen; Guido Baldi; Paul Berenberg-Gossler; Geraldine Dany-Knedlik; Hella Engerer (DIW Weekly Report, 2021)
The resurgence of the pandemic and renewed lockdowns have slowed the recovery of the global economy, but the overall losses will be less severe than after the first coronavirus wave in spring 2020. Industry in particular continues to develop well. In contrast, retail trade and personal services have been heavily affected, especially in hard-hit regions such as Europe. However, the fiscal stimulus cushions much of the distortions. With increasing levels of immunity, most economic restrictions will be lifted beginning in the second half of 2021, which should boost private consumption. Due to strong growth in the US and China, DIW Berlin is increasing its forecast by 0.4 percentage points for both 2021 and 2022 and expects growth of 6.7 and 4.8 percent for each year, respectively. Global production should first be able to reach its long-term growth path by the end of 2022. Although the Brexit Deal and the end of Donald Trump's presidency have eased some global uncertainties, risks still remain, especially from new waves of coronavirus infections and sharp increases in insolvencies.
Keywords: E32; E66; F01; 330; business cycle forecast; economic outlook